Relações entre sensações sinestésicas, estados emocionais e estruturas musicais - Guilherme Francisco Furtado Bragança (2015)
The present study aims to investigate the relationship between the stimulus of sensations and emotions by listening to excerpts from music and their musical structure, comparing the perception of musicians and non-musicians. A review of the literature on sensation, perception, synesthesia and emotions aroused in listening to musical excerpts was taken, reinforcing the idea of the existence of a latent synesthesia, which can affect the creative process and perception. Perception tests with 68 subjects, equally divided between musicians and non-musicians, was conducted to investigate the existence of convergence in choosing synesthetic adjectives, the expression of emotional states and assigning colors to eight music snippets. Analysis of parameters of musical excerpts used in research, with the goal of understanding the relationship between musical structure and perceptions was conducted. We verified the existence of convergence on perception of sensations, emotions and colors for same musical excerpts within each group of musicians and non-musicians, and globally. We can perceive clear association between emotions, sensations and colors: Excerpts 1 and 5 aroused tranquility, softness and tended to bright blue; musics 2 and 4, which caused joy and sense of fluency, tended to yellow, excerpts 3 and 6 aroused sadness and heaviness and were both bimodal in color scale, tending to red and navy blue. Music 7, considered tense, dense and energetic, tended to red. Music 8 that for all volunteers was the most neutral on both emotions and sensations, tended to pale green. These results suggest that musical structure plays a key role in the induction of sensations and emotions, compared to subjective factors. It is also noticed influence of temporal parameters (tempo, pulse, rhythm and meter) on energy, and the combination of rhythm and parameter settings related to pitch (range, harmonic complexity, melodic structure, records) in the characterization of valence. Although musicians and non-musicians have noticed the same emotions in each piece of music, it can be noted that musicians scored slightly stronger emotions than non-musicians, which may indicate an influence of increased knowledge of musical language in the intensity of musical enjoyment.